The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1097/00007890-199907150-00015
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Outcomes of Liver Transplantation in Adults

Abstract: This medical and economic cohort study suggests that OLT is still expensive; the study identifies sources of extra cost that could be limited either by improved selection of patients or, in the future, by technological advances in immunosuppressive therapy that help avoid medical complications. It also suggests the situation is precarious, with outcomes and costs being very sensitive to variation in graft availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
0
11
1
1
Order By: Relevance
“…Several studies have reported the financial costs of DDLT (10,11), but the data regarding the financial burden associated with LDLT are limited by small patient numbers (12 …”
Section: the Impact Of Ldlt On Patient Outcomes Remains Controversimentioning
confidence: 99%
“…Several studies have reported the financial costs of DDLT (10,11), but the data regarding the financial burden associated with LDLT are limited by small patient numbers (12 …”
Section: the Impact Of Ldlt On Patient Outcomes Remains Controversimentioning
confidence: 99%
“…3 Moreover, the economics, social burden, and ethical considerations of maintaining patients on waiting lists should also be taken into consideration. 4 Over the years, many clinical and biochemical parameters have been suggested in order to more accurately predict the prognosis of cirrhotic patients and correctly assess their short and medium term survival. The Child-Pugh score is still considered the cornerstone in the prognostic evaluation of cirrhotic patients although it was formulated more than 30 years ago.…”
mentioning
confidence: 99%
“…Retransplantation is known to have a significant impact on cost of care of transplant recipients. 28,35,36 However, in this series, retransplantation was not identified as a predictor of cost. A significant difference in cost of transplantation and care in the first year persisted after the 2 patients (1 LDLT and 1 CDLT) who were given retransplantation during their initial transplant visit are excluded from the analysis.…”
Section: Discussionmentioning
confidence: 60%